FACTORS FOR AUTOMATIC EARLY WARNING SCORING IMPLEMENTATION IN MALAYSIAN PRIVATE HOSPITALS - Perjit Singh; Chun Hong Loh; Nabsiah Abdul Wahid, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The paper explored factors affecting the choice of early warning score (EWS) card adoption using the case study of Malaysian hospitals. One hundred hospitals in Malaysia participated in a survey where CEO’s and nursing directors filled semi-structured questionnaires. A review of current literature confirms that deteriorating health following treatment of acute health is a critical issue undermining sustainable marketing in healthcare. Lack of sufficient and efficient measures to effectively care for these patients promptly has continued to present challenges to healthcare providers. Part of the problem is that it has always been problematic to detect early warning signs and calls when vital signs appeared. While early warning signs have been adopted to respond to calls of vital signs, difficulties arise in terms of efficient documentation, recording, interpretation and implementation of EWS. Hospitals with limited financial capabilities are compelled to use manual early warning scores. EWS is relatively affordable to acquire, install and maintain. They, however, lack in efficiency, timeliness and accuracy. The present study revealed that only seven hospitals had implemented manual early warnings signs. Findings indicated that no hospitals have implemented automatic warning signs, despite respondents indicating their understanding of the benefits and complexity associated with automation of EWS. The management of these hospitals revealed the high cost of implementing and maintaining automated EWS and inability to measure outcomes as the top reasons for not having automated EWS. However, the study noted that leadership and ethics, especially the leader’s attitude, employee’s engagement and perceived benefits of automatic EWS have a role in determining the successful implementation of EWS. To successfully implement EWS as a powerful marketing strategy, good management for implementation should be in place.